Acute Colonic Pseudo-Obstruction: A critical complication in burn patients. Issue 1 (January 2022) - John, Albin A.; Anand, Rohan; Frost, Joshua; Griswold, John A.
Highlights: Acute Colonic Pseudo-Obstruction (ACPO) is a critical preventable concern in severely burned patients. Neostigmine use should be a temporizing measure rather than a tool for definitive resolution of ACPO. Early surgical intervention should be used for definitive resolution of ACPO if Neostigmine fails. Abstract: Acute Colonic Pseudo-Obstruction (ACPO) is a rare diagnosis characterized by gross dilation of the large bowel in the absence of an obstruction in burn patients, traditional management of ACPO may not be successful in fully resolving the bowel distention without recurrence, necessitating a more aggressive management course. We present five such patients from our Regional Burn Center and their clinical course. This case series aims to raise awareness for this rare yet significant complication of burn trauma, with recommendations for adjusted management algorithms.